Study guides

Q: What is the result of isolating y2 in the equation below?

Write your answer...

Submit

Related questions

y2=-x2-8x+6

4

The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.

11 = sqrt of 121. it is a circle centred on the origin think what would happen on the line x=0 (The y axis) the equation simplifies to y2 = 121 or y =11 you can also think of eqn of a circle as x2+y2=r2

1

x2 + y2 = 2r2

t

Type your answer here. Find the radius for a circle with the equation x2 plus y2 equals 9? ..

You cannot solve it since only one side of an equation is given. If the equation was y4 + 5y2 - 84 = 0 then y4 + 12y2 - 7y2 - 84 = 0 or y2*(y2 + 12) - 7*(y2 + 12) = 0 or (y2 - 7)*(y2 + 12) = 0 then y2 = 7 or y2 = - 12 y = +or- sqrt(7) and, if you are in the complex domain, also y = +or- i*sqrt(12) where i is the imaginary square root of -1.

y2=x3+3x2

Equation of a circle centre the origin is: x2 + y2 = radius2 ⇒ radius = √9 = 3.

The equation is: x2+y2 = radius2

5. A circle with centre (0,0) has equation: x2 + y2 = radius2 With: x2 + y2 = 25 = 52 The radius is 5.

If this is the equation of a circle, the answer is 11, except that there needs to be a plus sigb between the x2 and the y2

Standard equation for a circle centred at the origin is x2 + y2 = r2 where r is the radius of the circle. If you increase the size of the circle then the radius must increase, so r2 will be larger. eg a circle of radius 2 has the equation x2 + y2 = 4, if the radius increases to 3 then the equation becomes x2 + y2 = 9

Since the circle is centered at the origin, the equation of the circle is x2 + y2 = r2. So we have: x2 + y2 = (3/2)2 x2 + y2 = 9/4

8

Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68

the equation is A= y2-y2/x3-x2 after that you find the y-intercept by doing, b= y1+y2+y3-A(x1+x2+x3)/3

The equation (y2-y1)/(x2-x1) is known as the point-slope formula. It gives the slope for a line given two points of coordinatesÊ(x1, y1) and (x2, y2).

x2 + y2 = 49

(y2-y1)(x2-x1) you plug in the equation to this formula and thats ur answer!

The slope between two points, (x1, y1) and (x2, y2) is: (y1 - y2) / (x1 - x2)

The mid-point of the line segment of (x1, y1) and (x2, y2) is (x1+X2)/2 and (y1+y2)/2

y2 = 169 Square root both sides: y = 13

People also asked